Safety and Efficacy of Long-Term Use of Extended Release Cornstarch Therapy for Glycogen Storage Disease Types 0, III, VI, and IX - Ross, Katalin M.; Brown, Laurie M.; Corrado, Michelle M.; Chengsupanimit, Tayoot; Curry, Latravia M.; Ferrecchia, Iris A.; Porras, Laura Y.; Mathew, Justin T.; Dambska, Monika; Weinstein, David A. (Journal of Nutritional Therapeutics, 2016)
Background: Impaired glycogen release with fasting results in hypoglycemia in the glycogen storage diseases. A waxy-maize extended release cornstarch was introduced in the United States in 2012 to maintain glucose concentrations during the overnight period, but no studies have assessed the long-term safety and efficacy of this product in the ketotic forms of GSD. Objective: To assess long-term safety and efficacy of modified cornstarch in patients with ketotic forms of GSD. Design: An open label overnight trial of extended release cornstarch was performed. Subjects who had a successful trial (defined as optimal metabolic control lasting 2 or more hours more than with traditional cornstarch) were given the option of continuing into the long-term observational phase. Participants were assessed biochemically at baseline and after 12 months. Results: A total of 16 subjects participated in the open label trial. Efficacy was demonstrated in 100% of the subjects with GSD 0, III, VI, and IX. Of the patients who entered the longitudinal phase, long-term data are available for all subjects. The mean duration of overnight fasting on traditional cornstarch prior to the study for the cohort was 4.9 hours and 9.6 hours on the extended release cornstarch (P < 0.001). All laboratory markers of metabolic control have remained stable in the chronically treated patients. Conclusion: Extended release cornstarch dramatically prolongs the overnight fast duration, maximizes safety from hypoglycemic events, reduces the possibility of sleep deprivation, and improves the quality of life of patients by eliminating the need to awaken without fail for middle of the night therapy without sacrificing metabolic control.